SUBSTANTIVIZATION OF ADJECTIVES - Teshaboyeva Nafisa Zubaydulla qizi; Sheraliyeva Shoira To’lqin qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The substantivization of adjectives in English is a remarkable linguistic process where adjectives function as nouns, enabling them to represent concepts, groups, or abstract ideas. This phenomenon plays a crucial role in the grammatical, semantic, and stylistic richness of the English language. Substantivized adjectives, such as the rich, the unknown, and the brave, allow for concise expression of complex notions while retaining a link to their adjectival roots. This article explores the types of substantivization—complete, partial, and contextual—alongside their historical development and syntactic behavior. Additionally, it highlights the stylistic functions of substantivized adjectives in literature, formal discourse, and modern usage. The findings demonstrate that substantivization not only reflects the flexibility of English grammar but also enhances its expressive capabilities, making it a vital area of study for linguists and language enthusiasts alike.